Addition of caffeine to equine thawed sperm increases motility and decreases nitrite concentration. (28th December 2020) - Alves, Natália de Castro; Diniz, Soraia de Araújo; Viegas, Rodrigo Novaes; Cortes, Steyner Franca; Costa, Eduardo Damasceno; Freitas, Marina Morra; Martins‐Filho, Olindo Assis; Araújo, Márcio Sobreira Silva; Lana, Ângela Maria Quintão; Wenceslau, Raphael Rocha; Lagares, Monique de Albuquerque
Abstract: The aim of this study was to improve the quality of frozen‐thawed equine sperm by the addition of caffeine to it. Semen from nine stallions was frozen and different concentrations of caffeine (3, 5 and 7.5 mM) were added to frozen‐thawed semen. The sperm kinetic parameters, membrane functionality and integrity, and acrosome integrity and spontaneous acrosome reacted sperm were evaluated with a computer‐assisted sperm analysis, a hypoosmotic swelling test and epifluorescent microscopy, respectively. Nitrite and hydroperoxide concentrations of frozen‐thawed semen were measured using spectrophotometry. Sperm fertility was evaluated by artificial insemination (AI) of 16 mares with thawed ejaculates (control and 5 mM caffeine‐treated groups). Compared to that in the control, the addition of 5 mM caffeine induced an increase in sperm motility (38.9 ± 2.8 versus 32.6 ± 3.4%), and a decrease in nitrite concentration (11.4 ± 2.1 versus 12.8 ± 2.9 µM/µg protein, p  < .05). Moreover, the pregnancy rate from AI in the caffeine group was significantly higher (62.5%) than that in the control group (12.5%). These data suggest that caffeine reduced the nitrite concentration and enhanced sperm motility in thawed equine sperm, thus increasing the fertility rate in mares inseminated with caffeine‐treated equine semen.